PENGGUNAAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA PEMBELAJARAN PA CIMAKH UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA KELAS III SDN 2 SUMAMPIR PADA TEMA 1 PERTUMBUHAN DAN PERKEMBANGAN MAKHLUK HIDUP - Maulidiya Shilvi Arifah; Sri Wahyuti; Elly Hasan Sadeli; Anang Fathoni (LPPM Universitas Bina Bangsa, 2023)
Language serves as a crucial tool for human thinking and interaction. The presence of the Indonesian language holds its own authentic value and uniqueness in Indonesia. However, within the realm of education, Indonesian language is often considered a challenging subject to learn. The aim of this research is to enhance the learning achievement of third-grade students in Theme 1 of the Indonesian Language subject, specifically focusing on the topic of growth and development of living beings, through the implementation of the Problem-Based Learning model aided by the Pa Cimakh learning media. This study falls under the category of Classroom Action Research (CAR). The research subjects comprised 29 third-grade students. Learning achievement data were collected through multiple-choice written tests and subsequently analyzed using descriptive statistics. The results of the research demonstrate notable improvements in learning achievement in each cycle. The attainment percentage for learning achievement in the first cycle was 34.48% with an average score of 64.14, in the second cycle it was 58.62% with an average score of 58.62, and in the third cycle, it reached 82.75% with an average score of 85.17. These findings substantiate that the application of the Problem-Based Learning model with the assistance of the Pa Cimakh learning media can effectively enhance learning achievement in Theme 1, Growth and Development of Living Beings, within the Indonesian Language subject in the third-grade class of SD N 2 Sumampir